Venture Advocate Behaviors and the Emerging Enterprise. (March 2016) - Saxton, Todd; Wesley, Curtis L.; Saxton, M. Kim
Abstract : Research summary: Venture founders rely on the help of others in their community to move their emerging enterprises forward. While these helping behaviors, here called venture advocate behaviors (VABs), are critical for founders with limited resources, they have received little theoretical or empirical attention. We explore VABs and develop propositions regarding a venture advocate's propensity to engage in such behaviors. Using social exchange theory, we examine how reciprocity between different actors, including paying back and paying forward, and other factors promote VABs. Managerial summary: Founders of new ventures need to understand the factors that encourage others to give them the help they need for their new firms to survive and grow—what we call venture advocate behaviors (VABs). A new firm that enables these VABs is able to access resources without a monetary burden because they are activated through social exchanges. In order to enable VABs, founders need to understand the individual characteristics of potential advocates, how they will assess the likelihood of success of the new venture, and the decision rules they will use, such as reciprocity, building socioemotional wealth, and the positive identification the potential advocate has within the local venture ecosystem. Copyright © 2016 Strategic Management Society.